Somatic characteristics and motor fitness of elite and sub-elite Polish male badminton players - Tomaszewski, P.; Keska, A.; Tkaczyk, J.; Nowicki, D.; Sienkiewicz-Dianzenza, E. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: An appropriate level of somatic and fitness traits is believed to contribute to success in an international badminton competitions however, these have not been sufficiently explored in elite Polish badminton players. Therefore, the aim of the study was to assess somatic build and physical fitness of elite and sub-elite Polish badminton players and to identify key traits that determine achieving sporting success in badminton. METHODS: The study participants comprised 20 men from the Polish Badminton National Teams A (elite; N.=9) and B (sub-elite; N.=11). In all participants body height, arm span, body mass, body fat, fat free mass and Body Mass Index (BMI) were assessed. Fitness tests included two badminton-specific on-court movement tests and cycloergometer test to assess maximal oxygen uptake (VO2max). RESULTS: Studied players did not differ in body height and arm span however, elite players were heavier by about 10 kg and had significantly higher values of BMI and body fat. Irrespectively of sport level, elite and subelite badminton players achieved comparable results in both on-court tests as well as with respect to VO2max (55.9 and 57.2 mL/min/kg, respectively). Cluster analysis allowed to indirectly describe the profile of somatic traits and physical fitness that facilitates achieving success in badminton. CONCLUSIONS: Relatively small body size of badminton players can be considered advantageous in sport competitions. It also seems that aerobic capacity contributes to achieving sport success in badminton to a much lower degree than the badminton-specific on-court skills.